2016
DOI: 10.1186/s13229-016-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered gaze following during live interaction in infants at risk for autism: an eye tracking study

Abstract: BackgroundThe ability to follow gaze is an important prerequisite for joint attention, which is often compromised in children with autism spectrum disorder (ASD). The direction of both the head and eyes provides cues to other people’s attention direction, but previous studies have not separated these factors and their relation to ASD susceptibility. Development of gaze following typically occurs before ASD diagnosis is possible, and studies of high-risk populations are therefore important.MethodsEye tracking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 46 publications
9
89
1
Order By: Relevance
“…In relation to the concurrent validity, the study found a moderate negative association between the general score of CARS-BR and the behavior "gaze at therapist". The finding is in accordance with the existent literature on communication for individuals with ASD where distinct publications postulate that gaze contact is a central ability to detect autistic symptoms and associated behaviors (d'Arc et al, 2016;Pell et al, 2016;Thorup, Nyström, Gredebäck, Bölte, & Falck-Ytter, 2016). Two validated instruments in MT (Individual Music-Centered Assessment Profile for Neurodevelopmental Disorders and Music-based Autism Diagnostics) for children with ASD consider gaze contact as a core characteristic to be detected by musical interaction (Bergmann et al, 2015;Carpente, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…In relation to the concurrent validity, the study found a moderate negative association between the general score of CARS-BR and the behavior "gaze at therapist". The finding is in accordance with the existent literature on communication for individuals with ASD where distinct publications postulate that gaze contact is a central ability to detect autistic symptoms and associated behaviors (d'Arc et al, 2016;Pell et al, 2016;Thorup, Nyström, Gredebäck, Bölte, & Falck-Ytter, 2016). Two validated instruments in MT (Individual Music-Centered Assessment Profile for Neurodevelopmental Disorders and Music-based Autism Diagnostics) for children with ASD consider gaze contact as a core characteristic to be detected by musical interaction (Bergmann et al, 2015;Carpente, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…In the eye tracking session, the infant was seated in the parent’s lap at a distance of ~200 cm from a test leader sitting behind a low table (the same setup as Thorup et al 2016, see Supplementary Information for an illustration). The gaze of the infant was recorded using a Tobii TX300 eye tracker without a monitor, which is suitable for infant eye tracking with live stimuli, placed between the infant and the test leader.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one study found that looking time at the mother’s mouth in infancy was associated with larger vocabulary in toddlerhood, suggesting that early attention to rich and continous (visual and audiovisual) information available from this part of the face may have boosted the development of language skills (Young et al 2009), and for related face processing studies focusing on the still face procedure, see Merin et al 2007; Cassel et al 2007. Studies of joint attention have also shown a link between gaze behavior and language aquisision (Morales et al 2000; Yoder et al 2006), and documented early alterations in infants at risk for autism (Presmanes et al 2007; Thorup et al 2016). While these studies [and many others, including Mundy and Newell (2007); Mundy and Crowson (1997); Bedford et al (2012), etc.]…”
Section: Introductionmentioning
confidence: 99%
“…A review of 122 studies indicated atypical gaze patterns across the lifespan in people with ASD, consistent with fundamental deficits in selecting and attending to information needed to perceive social interactions accurately 88. Numerous studies have examined early correlates of these findings in high risk infants 89909192939495969798. Several of these have focused on cross sectional group differences in visual orienting between high risk and low risk infants in relation to face processing,92959699 gaze following,8998 and language processing 91.…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%